2017
DOI: 10.1021/acs.macromol.6b02206
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Deformation of Glassy Spherical Microdomains in Elastomeric Triblock Copolymer Films: Simultaneous Measurements of a Stress–Strain Curve with 2d-SAXS Patterns

Abstract: Thermoplastic elastomers are elastomeric materials which contain hard domains as physical cross-linking for rubbery chains. Therefore, the hard domains are required permanently rigid. Nevertheless, we have found experimentally deformation of the hard domains upon uniaxial stretching of the thermoplastic elastomer films. In this paper, we report experimental results of deformation of glassy spherical microdomains in elastomeric triblock copolymer films upon uniaxial stretching, as revealed by two-dimensional sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 32 publications
(60 reference statements)
5
36
0
Order By: Relevance
“…Overall, the stressstrain curves follow the expected behavior, with the stress increasing with the fraction of the glassy A component in the sample. Consistent with prior results from simulations 20,58 and experiments 27,60 , the absolute stress is highest for the lamellar morphology, followed by cylindrical morphology, with the spherical morphology having the lowest stress.…”
Section: A Equilibrium Propertiessupporting
confidence: 89%
“…Overall, the stressstrain curves follow the expected behavior, with the stress increasing with the fraction of the glassy A component in the sample. Consistent with prior results from simulations 20,58 and experiments 27,60 , the absolute stress is highest for the lamellar morphology, followed by cylindrical morphology, with the spherical morphology having the lowest stress.…”
Section: A Equilibrium Propertiessupporting
confidence: 89%
“…The orientation of the PEB chains during sample deformation is also crucial for understanding the mechanical properties of the material. In situ small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) techniques are powerful methods to investigate the arrangement and deformation behavior of PS domains as well as the orientation state of the PEB chains. Many studies have reported on the deformation behavior of various types of thermoplastic elastomers based on these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the interdomain distance increased with increasing strain in the stretching direction, as observed from a change in the scattering intensity distribution from the SAXS results. Sakurai et al investigated the quantitative deformation of PS domains containing in thermoplastic elastomers under uniaxial elongation using simultaneous SAXS measurements . They clarified that the glassy domains deformed to prolate spheroids during uniaxial stretching.…”
Section: Introductionmentioning
confidence: 99%
“…For block copolymer systems, 2DSPs were extensively observed to study structural changes due to shear or uniaxial deformations [32,33,34,35,36,37,38,39,40,41,42]. For example, Betes et al [32] reported the dependence of the order–disorder transition in poly(ethylene-propylene)–poly(ethylethylene) (PEP–PEE), a diblock copolymer, on the shear rate; two-dimensional contour plots of the two phases show changes corresponding to those in scattering patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Krishnamoorti et al conducted neutron scattering experiments to examine 2DSPs during a cylinder-to-sphere order–order transition in block copolymers [37]. Sakurai and co-workers examined 2DSPs of strain-induced deformation of glassy spherical micro-domains in elastomeric triblock copolymers [38,39,40]; they also measured the stress as a function of strain in these systems. Mao et al and McCready and Burghardt reported changes in 2DSPs corresponding to deformation of re-oriented micro-domains in a hexagonally ordered styrene–ethylene–butylene–styrene (SEBS) triblock copolymer under uniaxial extensional flow [41,42].…”
Section: Introductionmentioning
confidence: 99%